Formando-se professor(a) da educação infantil: a escola com contexto - Oliveira, Milena Paula Cabral de (2011)
This work is the result of a set of experiences and reflections on teaching in kindergarten and, in particular, the issues raised by first experiences as a teacher and how these issues were being gradually answered from the experience in a school . Guided by these experiences and studies of Oliveira-Formosinho (2002) on the training of kindergarten teachers in the school context, among others as: Barreto, Kuhlmann Jr. (1998), Vasconcelos et. al. (2000); Nóvoa (1992, 1995), Moita (1995), Freire (1996), Tardif (2002, 2009) Kramer (2005) and Hargreaves, Fullan (2000), built as study questions: what situations become in the context of professional training at an institution of early childhood education? Which subjects who took part? How involved? From this perspective the goal of our work is a: to investigate, from the perspective of teachers a public kindergarten, situations of professional interaction that become the context of teacher education. The research took the principles of qualitative approach and an intrinsic case study (STAKE, 1998), whose locus was a Municipal Center for Early Childhood Education, so defined by their peculiarities for training faculty in the context of practice. We built the data with a group of nine teachers CMEI this by conducting a questionnaire, interviews and document analysis. Data analysis, guided by the principles of content analysis, allowed to note that beyond the initial training and personnel, the school context contributes to its fundamental training for teachers of kindergarten, whereas their specificities. We conclude by confirming that systematic and unsystematic in situations developed in the school routine, interaction with peers and other members of the school, the teachers take ownership of specific knowledge specific to teaching in kindergarten